Model prediksi kebangkrutan pada perusahaan perusahaan properti-konstruksi di Indonesia - Hendra Kusmartono; Toto Rusmanto (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the Altman, Grover, and AAN models in predicting the bankruptcy of construction-property companies in Indonesia. Sample selection used the purposive sampling method, and the sample is property and construction companies listed on the Indonesia Stock Exchange. Data analysis used Hit Ratio followed by Kruskal Wallis and Mann-Whitney statistical tests. The analysis of bankruptcy predictions using the Altman method obtained that in 2015 there were two issuers grouping bankrupt companies; in 2016, 2017, and 2018, there were four issuers, and five issuers in 2019. The Grover method predicted two issuers to go bankrupt in 2016, four issuers in 2017, three in 2018, and five in 2019. The bankruptcy prediction of the AAN method shows that there are 18 issuers (2015), 19 issuers (2016), 22 issuers (2017), and 20 issuers (2018). Based on the Hit Ratio value, the accuracy of the Altman method is 88.85%, the Grover method is 90.38%, and the AAN method is 61.54%. There is a significant difference between the accuracy of the Grover method, Altman and the AAN method. The best order of accuracy in predicting bankruptcy is the Grover, Altman, and AAN methods.